Whistleblowing Intentions in Fraud Cases: The Interplay of Organizational Culture and Personal Ethic - Riza Aulia Rachman; Ingka Ulupui; Indra Pahala (PT FORMOSA CENDEKIA GLOBAL, 2025)
Whistleblowing is a crucial mechanism for uncovering fraud and unethical behaviour within organizations, yet the decision to report misconduct is influenced by a complex interplay of organizational culture and personal ethics. This study explores the factors that drive employees to report fraud, focusing on how organizational culture and personal ethical beliefs interact to shape whistleblowing intentions. A systematic literature review (SLR) was conducted to synthesize recent studies from 2019 to 2024, analysing the role of ethical climates in organizations and individual moral values. The findings suggest that organizational culture significantly influences whistleblowing behaviour, with supportive and transparent environments fostering higher rates of reporting. Personal ethics, such as moral intensity and a sense of duty, also play a critical role, although their effect is moderated by the organizational context. The study highlights the importance of aligning personal ethical standards with organizational culture to encourage whistleblowing and reduce fraud. Recommendations for practice include creating a culture of ethical leadership, providing clear whistleblower protection policies, and promoting a transparent and supportive reporting system.